New syllabus mathematics workbook 2 7th edition - Yeo,Dr Joseph; Teh Keng Seng (Karachi: Oxford university press, 2018)
New Syllabus Mathematics Workbook 2 is a supplementary resource designed to support students in mastering key math concepts aligned with the current curriculum. It includes a variety of practice questions, worked examples, and problem-solving exercises that build skills in areas such as algebra, geometry, and data handling. The workbook helps reinforce classroom learning, promotes independent study, and prepares students for more advanced mathematics through structured and progressive exercises.
The New Syllabus Mathematics Workbook 2 is designed to complement the main textbook in developing students' understanding and mastery of key mathematical concepts typically covered in the second year of lower secondary education. Aligned with the latest curriculum standards, this workbook provides a wide range of practice problems, skill-building exercises, and real-life applications aimed at reinforcing classroom learning.It focuses on critical areas such as algebra, geometry, number theory, and data handling, while also encouraging logical thinking and problem-solving skills. The exercises are structured progressively to support students of varying ability levels, ensuring that foundational concepts are well understood before moving on to more complex tasks.
Keywords: Algebraic Expressions; Simultaneous Equations; Linear Equations and Inequalities